Facile layer-by-layer self-assembly of 2D perovskite niobate and layered double hydroxide nanosheets for enhanced photocatalytic oxygen generation. (6th October 2021) - Zheng, Botong; Mao, Liuhao; Shi, Jinwen; Chen, Qingyun; Hu, Yuchao; Zhang, Guiquan; Yao, Jiantao; Lu, Youjun
Abstract: Photocatalytic O2 -generation reaction is recognized as a crucial step in water splitting and has drawn great attention of researchers. In this work, a hetero-layered composite photocatalyst was successfully prepared by a facile self-assembly method based on electrostatic interaction between oppositely charged Zn/Cr-layered double hydroxide (Zn/Cr-LDH) and lead niobate nanosheets. The layer-by-layer stacking of Zn/Cr-LDH and HPb2 Nb3 O10 nanosheets was beneficial for rapid migration of photo-induced charge carriers inside the photocatalyst because of large contact area. In the meantime, Zn/Cr-LDH and HPb2 Nb3 O10 components exhibited suitable energy-band alignment, which led to efficient separation of photo-induced charge carriers. The composite photocatalyst showed enhanced photocatalytic O2 -generation activity under visible-light irradiation without loading cocatalyst. Briefly, this work expanded the applications of AB2 Nb3 O10 -based materials in photocatalytic energy conversion and proved that constructing composites based on electrostatic self-assembly of complementary 2D materials is a promising strategy for development of more efficient photocatalysts. Graphical abstract: Image 1 Highlights: Zn/Cr-LDH-Pb2 Nb3 O10 hybrid system was prepared by facile self-assembly method. Large contact area between different nanosheets facilitated the inner migration of charge carriers. Suitable band alignment enhanced efficient separation of the photo-induced charge carriers. Hybrid system exhibited improved photocatalytic performance without co-catalyst.